Response of upland rice (Oryza sativa L.) cultivars to different shade levels in sandy soil - Irwan Suluk Padang; Tohari Tohari; Jaka Widada (Jurnal Ilmu Pertanian, 2020)
The study aimed to determine the response of upland rice under different shade levels. The experiment was conducted in Srigading village, Sanden District, Bantul Regency, Yogyakarta from July 2016 to March 2017. The experimental design applied was the split-plot design with three replications. The main plot was the shade level consists of three levels i.e. 0%, 25% and 50%. The sub plot was the upland rice cultivar consists of three levels i.e.  ‘Inpago 8’, ‘Situ Patenggang’, and ‘Batutegi’. The results showed that some variables observed changes due to shade that are make increased the plant height and leaf area. The maximum number of tillers and the number of productive tillers in the 50% shade treatment decreased, as well as the total plant dry weight and the productivity. Other observation such as root/shoot ratio, panicle length, percentage of filled grain per panicle, number of filled grains per panicle and 1000-grains weight upland rice showed no significant difference.